2017
DOI: 10.1093/pubmed/fdx132
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Brazilian Family Health Strategy and the conditional cash transfer on tuberculosis treatment outcomes in Rio de Janeiro: an individual-level analysis of secondary data

Abstract: This is the first individual-based study to show a relevant protection of poor urban communities regarding patient-important health outcomes by the Brazilian FHS and CTP. These findings support strategies of universal health coverage, primary care strengthening and social protection to achieve a major SDG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 25 publications
(29 reference statements)
2
34
0
2
Order By: Relevance
“…This overlap suggests that we are only comparing patients with similar covariate profiles: while some of the control patients may not be eligible on paper for Bolsa Familia, in the complex context of real-world receipt of BFP, the controls resemble almost exactly those patients who receive it and are representative of a broad range of TB patients from across Brazil. This is a methodological improvement over the control groups seen in prior work which greatly strengthens the quality of evidence available to policymakers [7,10].…”
Section: Discussionmentioning
confidence: 85%
“…This overlap suggests that we are only comparing patients with similar covariate profiles: while some of the control patients may not be eligible on paper for Bolsa Familia, in the complex context of real-world receipt of BFP, the controls resemble almost exactly those patients who receive it and are representative of a broad range of TB patients from across Brazil. This is a methodological improvement over the control groups seen in prior work which greatly strengthens the quality of evidence available to policymakers [7,10].…”
Section: Discussionmentioning
confidence: 85%
“…3 In addition, the existence of a direct effect of BFP didn't preclude the hypothesis that other causal pathways were involved in the causal model and the importance of other determinants, as showed in previously published studies. [4][5][6] Bearing in mind that directed acyclic graphs allow us to assess different aspects of an association between covariates in a study, we are only just starting to explore this association, and there is a broad field to be explored. The next steps should be to look for the total effect of BFP by estimating the indirect effects of all causal paths and trying to explain the causal mechanisms.…”
mentioning
confidence: 99%
“…These findings corroborate those of previous studies that have found positive associations of government direct income transfer programs with success/cure following treatment. 14,15,16 The association between social protection strategies and successful treatment and cure of individuals with TB was also observed in a meta-analysis of studies carried out in Brazil and in other countries with similar levels of income and disease burden. 11 Among the limitations of our study, we include (i) the absence of data on the length of time and/or discontinuity of benefit receipt during treatment, given that such information was obtained at the time of diagnosis, (ii) the absence of measurement of the frequency of receipt of each benefit and the number of beneficiaries in each family affected by the disease and (iii) the possibility of non-response bias, since some participants were reluctant to report receipt of benefits for fear of losing them.…”
Section: Tuberculosis Treatment Outcome and Social Benefits In Salvadmentioning
confidence: 69%
“…2,10 Despite scarce knowledge on access and coverage of social programs and benefits for people with TB, recent evidence has pointed to their direct 15 or indirect positive effects on the improvement of treatment outcomes of these individuals, especially the poorest ones. As these findings relate only to the Bolsa Família program, [13][14][15][16] new studies are needed to investigate the effects of other social protection benefits on TB indicators. The Bolsa Família program is the most relevant social program in Brazil and one of the largest in the world.…”
Section: Education Level (In Years Of Schooling )mentioning
confidence: 99%
See 1 more Smart Citation